Lagrangian particle tracking in deforming sliding mesh for rotorcraft icing applications - Morelli, M.; Bellosta, T.; Guardone, A. (My University, 2019)
Particle tracking techniques are presented for simulating the development of clouds containing supercooled water droplets entrained in complex flow systems such as those produced by rotorcraft. The physics of this problem and the associated condition is known as in-flight icing, where extreme ice structures can possibly form, causing severe performance degradation and a reduction in handling qualities. Resolving rotorcraft flow fields frequently entails the use of multi-zone and deforming grid systems to allow independently moving components. The approach advocated here allows particle tracking through mesh with arbitrary motion which includes deformation and particle tracking through non-conformal interfaces which are present in multi-zone problems. These techniques are first described and verified for two-dimensional problems before the results of three-dimensional practical engineering applications are shown.